Disturbance and regeneration of swam forest in Nicaragua: Evidence from ecology and paleoecology / Gerald R. Urguhart, - Urguhart, Gerald R. (1997)
The natural history of central American raphia taedigera mart, swamps, low diversity, monodominance, seasonal and permanent flooding, sea level rise and diversity catastrophic disturbances and regeneration; major regions of swamp forests of southern central America, east and southeast Nicaragua, pre-fire swamps, interior of damageg swamp forests, riverbanks, northeast costa Rica; patterns and mechanisms of early succession in hurricane and fire-damaged swamps, the ecology of raphia taedigera mart, (arecaceae) and its interactions with blechnum serrulatum rich, pteridophyta, blechnaceae, methods, raphia growth, raphia removal; flood-tolerance and flood-escape mechanisms of seeds and seedlings of common swamp trees of central America, materials and methods, seed sources, seed germination; Holocene record of the formation and development of a Nicaragua swamp, material and methods, coring paleoecological methods; paleoecological evidence of raphia in the pre-Columbian neotropics, methods, resilts, discussion, references; paleoecological persistence of raphia taedigera mart, swamps, methods, site description, paleoecological methods.